What sectors should the countries’ climate policies prioritize? - Conclusions derived from Norway vs Sweden - Oh, Eugenia (Technium Sustainability, 2025)
While each country is making movements to address climate issues, their engagement varies greatly. While countries must take active steps to reach the goals set by the Paris Agreement and other international agreements, some countries seem to be far away from the achievement of the goal. In this paper, the author aimed to determine the direction all country’s climate policies must pursue by comparing two countries with similar geographical and economic conditions but different reduction rates in GHG emission: Norway and Sweden. Through analysis of population, climate policies in all sectors (energy, industrial processes and product use, agriculture, and waste), and other events with indirect effects on GHG emissions, it was concluded that the discrepancy in reduction rates is derived from the stringency of energy policies. Thus, this paper claims that countries must focus primarily on the energy sector when implementing policies.